Distillation Control, Optimization, and Tuning - Robbins, Lanny (Taylor & Francis, 2025)
With a focus on the fundamentals and strategies of distillation columns, this book covers the process variables for continuous distillation columns, as well as four basic control strategies and the typical cases in which they are used. The author defines the inlet and outlet streams and process variables for a distillation column and then explains the overall concept of the separation and purification that is performed. Performance and product quality are described in terms of specification requirements, and tools and techniques for the optimization of quality performance are provided. Figures and graphs are included within the reference to illustrate concepts.